Diagnosis and treatment of Robert’s uterus combined with transverse uterine septum: a case report and review of the literature - Chen, Mingqian; Yang, Xiaoyu; Zhang, Bin; Fu, Jialiang; Lan, Yi; Chi, Yugang (Frontiers in Medicine, 2024)
Background Robert’s uterus combined with transverse uterine septum is a rare uterine malformation. Only one case has been reported to date, and it is challenging to diagnose and treat. Case presentation Here we report the case of a 19-year-old female had undergone multiple treatments at a previous hospital for primary amenorrhea and periodic lower abdominal pain, with the cause remaining unclear. Ultrasonography and magnetic resonance imaging conducted at our hospital displayed the presence of uterine dysplasia with an incomplete septum. Following a multidisciplinary discussion, a preliminary diagnosis of Robert’s uterus combined with transverse uterine septum was made. Following this, laparoscopic exploration and ultrasound-guided hysteroscopic metroplasty were performed. The patient experienced periodic menstruation postoperatively and did not manifest periodic lower abdominal pain. Conclusion Robert’s uterus combined with transverse uterine septum is a very rare uterine malformation, with hysteroscopic metroplasty being the preferred surgical option. Nevertheless, preoperative diagnosis is extremely difficult, and there are also many difficulties in the surgical process. This case outlines the diagnostic and treatment process of a patient with Robert’s uterus and transverse uterine septum. It is of great significance to fill the gap in clinical diagnosis and treatment of this special uterine malformation.